Política Pública, Governança e Capacidade Estatal: Programa de Proteção Social do Ttac em Linhares-es, no Contexto do Desastre da Samarco-fundão - Landín, Guadalupe Alexandra Vargas (2021)
The research object of study was the Social Protection Program (PPS) implemented by the Renova Foundation in the municipality of Linhares, state of Espirito Santo (ES), affected by the collapse of the ore tailings dam in Fundão-MG, belonging to the Samarco mining companies S/A, Vale S/A and BHP Billiton Ltda. This program was defined by the Transaction and Conduct Adjustment Agreement (TTAC), Subsection 1.5 (Clauses 54 to 58), signed between the mining companies and the Brazilian State, on 03/02/2016. As an objective, the research sought to launch an understanding of the actions, articulations and tensions between the Renova Foundation and the government (CTOS/CIF and SEMAS), in the program's implementation process. This process was carried out within the scope of the governance system created by the TTAC, which linked the execution of the program to public policies for Social Assistance and respective legislation in force. The research is theoretically anchored in the literature on state capacities and multi-stakeholder governance systems. The methodology used was the case study, the main instruments being documentary research and interviews. As a result, the main impasses and conflicts that punctuated the process of defining the program's action plan were highlighted. Five years after the disaster, until the end of the data survey, in December 2020, it had not yet been approved by the Interfederative Committee (CIF). As a result, the affected communities ended up being doubly harmed: at the time of the disaster and after the disaster. This, both due to the delay caused by the impasses that prevent the execution of the program, as well as the constant non-compliance with the guidelines and deadlines notified to the Renova Foundation, by the CTOS/CIF in its role as a State body, guaranteeing compliance with the TTAC.